ANALISIS KECURANGAN PELAPORAN KEUANGAN BERDASARKAN FRAUD DIAMOND THEORY (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2015-2019) - Patricia Alvionika; Wahyu Meiranto (Diponegoro Journal of Accounting, 2021)
Financial statements become an important instrument in the operations of a company. The financial statements reflected to the company’s financial condition. However, there are many loopholes in the financial statements that may provide opportunities for management or certain people to commit fraud in the financial statements. This study was conducted to analyze the effect of The Fraud Diamond developed by Wolfe and Hermanson (2004). These variables are external pressure, financial stability, financial targets, ineffective monitoring, rationalization, and capability with dependent variable is fraudulent financial reporting was proxied by earnings management.            The population in this study were banking companies listed in Indonesia Stock Exchange with the sample used in this study are 39 banking companies that listed in Indonesia Stock Exchange during the period 2015-2019. The type of data used are secondary data, in the form of annual reports of companies listed on the Stock Exchange during the period 2015-2019. Hypothesis testing was conducted using multiple regression with IBM SPSS 21 software.            The result showed that the variables of external pressure which proxied by Debt Leverage and capability which is proxied by the ratio of independent board shown to negative effect and significant to fraudulent financial reporting. Meanwhile, variables of financial stability was proxied by Loan to Deposit ratio, financial target which is proxied by Return on Assets, ineffective monitoring which is proxied by audit quality, and rationalization was proxied by change in external auditor shown negative but nonsignificant effect to fraudulent financial reporting.